Worthy Transfers? A Dynamic Analysis of Turkey's Accession to the European Union - Gül Ertan Özgüzer; Luca Pensieroso (Izmir University of Economics, Department of Economics, 2010)
We build a two-country dynamic general equilibrium model to study whether European citizens would benefit from the eventual accession of Turkey to the European Union. The results of the simulations show that Turkey's accession to the European Union is welfare enhancing for Europeans, provided that Turkish total factor productivity (TFP) increases sufficiently after enlargement. In the model with no capital mobility, the Europeans are better off if the Turkish TFP increase bridges more than 31% of the initial TFP gap between Turkey and the European Union. That figure becomes 45% when capital mobility is introduced.
Keywords: F41; 330; European Union; Turkey; Enlargement; Dynamic General Equilibrium; Open Economy Macroeconomics; EU-Mitgliedschaft; Türkei; Wohlfahrtsanalyse; EU-Staaten; Allgemeines Gleichgewicht; Zwei-Länder-Modell; Offene Volkswirtschaft; Theorie